Design of adjustable compliant mechanism for service robot - Al-Jothery H.K.M.; Sahari K.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Ball bearings; Compliant mechanisms; Environmental impact; Machine design; Mechanisms; Robotics; Robots; Stepping motors; Stiffness; Adjustable mechanisms; Flat plate; Mechanical compliance; Mechanical elements; Planar robots; Rectangular cross-sections; Robotic technologies; Variable stiffness; Multi agent systems